Implementasi Kebijakan Penyelenggaraan Perlindungan Anak Jalanan di Kantor Dinas Sosial Kabupaten Gowa - Abdul Sahid; Ambo Masse (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
Street children are a social phenomenon that demands serious attention from the government and society at large.with the implementation of the policy for the protection of street children at the gowa district social services office, it is hope that this can provide the best solution for them. This research uses qualitative research with a apopulation of 76 people and a sample of 20 people, based on the results og the research, it shows that the implementation of policies for managing street children is carried out by preventing the growth of children living on the streets, raiding children the streets, and are fostered, and taken to an orphanage where they gain knowledge and a decent life. Implementation always ends the formulation of policies that include programs and activities, thus, the Gowa district government made regional regulations ( PERDA ) number 05 of 2014 concerning the implementation of protection for street children in Gowa district social services, as the basis for development policies street children today.